Oxidative stability and shelf life of sunflower oil-in-water emulsions as affected by pro- and antioxidants and temperature - De Kock, Henrietta Letitia (University of Pretoria, 2019)
Thesis (PhD (Food Science))--University of Pretoria, 2019.